2006
DOI: 10.1097/01.aids.0000202651.41397.db
|View full text |Cite
|
Sign up to set email alerts
|

Survival and progression to AIDS in a seroconverter cohort in the post-highly active antiretroviral therapy era: effectiveness goes on

Abstract: Progression to AIDS and death for 1129 HIV seroconverters from the GEMES cohort were analysed by calendar period (1996-1997, 1998-1999, 2000 onwards). A further hazard reduction was observed for a later period for both. Intravenous drug users (IDU) had a faster progression. The results highlighted the importance of monitoring the effectiveness of highly active antiretroviral therapy and to improve public health strategies directed to IDU to reduce inequity in HIV infection care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 5 publications
2
11
2
1
Order By: Relevance
“…However, these results might be influenced by the fact that the study population includes a large proportion of MSM who are more likely to be closely monitored by HIV specialists and may therefore not be representative of the entire German population infected by HIV. A similar cohort study in Spain reported significant reduction in the risk of AIDS over calendar periods in comparison with the pre-HAART era, but there were no differences between the calendar periods in the post-HAART era [8]. However, the last observed calendar period was 20002003 and there were more IDU in the composition of this cohort than in our study.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…However, these results might be influenced by the fact that the study population includes a large proportion of MSM who are more likely to be closely monitored by HIV specialists and may therefore not be representative of the entire German population infected by HIV. A similar cohort study in Spain reported significant reduction in the risk of AIDS over calendar periods in comparison with the pre-HAART era, but there were no differences between the calendar periods in the post-HAART era [8]. However, the last observed calendar period was 20002003 and there were more IDU in the composition of this cohort than in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Just after the introduction of HAART in 1996, such studies showed a protective effect of HAART on time to acquired immunodeficiency syndrome (AIDS) [3-5]. Thereafter, continuous decrease on time to AIDS has been reported, coincident with the widespread uptake of HAART [6-8]. However, with ageing of the HIV-infected population, long-term exposure to treatment, varying adherence, emerging resistance and complications to therapies, there is a need to monitor regularly the effectiveness of HAART at the population level.…”
Section: Introductionmentioning
confidence: 99%
“…These factors cross all transmission routes and may confound or modify their effect on HIV. Highly active antiretroviral therapy (HAART) has led to a radical change in HIV prognosis,4 but there is a risk that the most vulnerable populations may be the least likely to benefit from available resources, contributing doubly to increased health inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Such treatment has led to a drastic reduction in mortality associated to the acquired immunodeficiency syndrome (AIDS), and to increased survival among HIV-infected individuals HIV (1). In the year 2009, the HAART response rate was very high, affording sufficient host immune recovery to allow the control of opportunistic infections, thanks to the introduction of increasingly well tolerated and simpler treatments such as the combination of several drug substances in a single tablet (2).…”
Section: The Late Diagnosis Of Hiv Infection In Spain; Magnitude Rismentioning
confidence: 99%